2005
DOI: 10.1381/0960892053576802
|View full text |Cite
|
Sign up to set email alerts
|

Development of Acute Gouty Attack in the Morbidly Obese Population after Bariatric Surgery

Abstract: Although rare, gout must be considered a co-morbid illness in obese and morbidly obese patients. Surgeons should be familiar with the signs and symptoms of attacks in the postoperative period, and be knowledgeable in the management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 7 publications
1
18
0
5
Order By: Relevance
“…Our data suggest that this increase may occur due to renal dysfunction associated with major surgery, although other metabolic effects due to fasting or rapid weight loss may also have contributed 23. Other groups have reported gout flares in the postoperative period in people undergoing bariatric surgery 24 25. This was also observed in one of our participants with established gout who developed a postoperative flare in the context of severe hyperuricaemia.…”
Section: Discussionsupporting
confidence: 83%
“…Our data suggest that this increase may occur due to renal dysfunction associated with major surgery, although other metabolic effects due to fasting or rapid weight loss may also have contributed 23. Other groups have reported gout flares in the postoperative period in people undergoing bariatric surgery 24 25. This was also observed in one of our participants with established gout who developed a postoperative flare in the context of severe hyperuricaemia.…”
Section: Discussionsupporting
confidence: 83%
“…No difference in the number of gouty attacks was observed in the control group . Antozzi et al reported a pre‐operative diagnosis of gout in 0.4% (5/1240) of a cohort of bariatric patients. Post‐operatively, two of the five patients experienced acute gouty.…”
Section: Discussionmentioning
confidence: 95%
“…As many turn to surgical means of weight loss, it is encouraging that a recent prospective study of 60 patients with type 2 diabetes and BMI ≥35 kg/m 2 found clinically significant reductions in serum uric acid levels one year after bariatric surgery (115). Interestingly, uric acid levels and gout attacks initially increase peri-operatively secondary in part to the catabolic effect of surgery, rapid weight loss, and renal impairment(115, 116). However, patients with weight loss post bariatric surgery ultimately benefit from reduced inflammation and show decreased production of interleukins including IL-1β, IL-6 and IL-8 in response to MSU crystals (117).…”
Section: Other Lifestyle Factorsmentioning
confidence: 99%
“…A study by Hanna et al actually reported lower serum uric acid levels in chronic smokers, though data was not adjusted for potential confounders such as BMI (116, 118). This confirmed findings from a prior cross-over study reporting decreased uric acid levels after smoking a cigarette (119).…”
Section: Other Lifestyle Factorsmentioning
confidence: 99%